Different Gender Priorities Amid EU Labor Laws and Practice - Sony, M M Abdullah Al Mamun (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Labor laws aim to accomplish a number of goals, including achieving gender equality in the workforce, to offer a minimum standard of living. The majority of academics, however, ignore other sexually inclined individuals like LGBTI in favor of accounting only for interactions between men and women to comprehend gender in its entirety. To close that disparity, this research used a comparative approach and a qualitative approach to investigate how the EU handles the issues of a varied labor force in terms of both law and physics. The EU, in contrast to other organizations, often gives its member states guidance by providing a range of consistent legal support. Based on secondary research, especially recent studies funded and supervised by the EU, this study found that although the EU has a comprehensive legislative measure to maintain women's labor rights, no unique legal structure has been formed that promotes LGBTI workplace rights. Because of this, most members of sexual minorities face discrimination at work and have trouble getting employment. The slow progress to reduce pay inequalities, pension disparities, and other forms of discrimination between binary and non-binary genders has revealed shortcomings in the current legal framework, even in the face of sufficient legal protections. The findings of this study have supported the implementation of regulations aimed at reducing gender-based wage and pension inequality as well as other forms of discrimination.